2018
DOI: 10.1039/c8ce00597d
|View full text |Cite
|
Sign up to set email alerts
|

Stacking of cyclopentadienyl organometallic sandwich and half-sandwich compounds. Strong interactions of sandwiches at large offsets

Abstract: 73% of stacking of Cp sandwiches in the CSD is at large offsets, since these interactions are relatively strong. Much weaker stacking between Cp half-sandwiches is surprising 60% of all stacks, due to more simultaneous interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…We show that these ligands can form some of the strongest anion-π interactions with halides, since the electrostatic potential surfaces above their ring centres can be positive. [36,51,52] Moreover, aromatic ligands in half-sandwich compounds are capable of forming even stronger CÀ H•••X À hydrogen bonds with halide anions, as well as σ-complexes, since electrostatic potentials at hydrogen atoms of aromatic rings are even more positive.…”
Section: Introductionmentioning
confidence: 99%
“…We show that these ligands can form some of the strongest anion-π interactions with halides, since the electrostatic potential surfaces above their ring centres can be positive. [36,51,52] Moreover, aromatic ligands in half-sandwich compounds are capable of forming even stronger CÀ H•••X À hydrogen bonds with halide anions, as well as σ-complexes, since electrostatic potentials at hydrogen atoms of aromatic rings are even more positive.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding these weak interactions has particular importance in the pharmaceutical sector, where a variety of fluorinated active pharmaceutical ingredients have been developed . This study is of special interest to the crystal engineering and structure simulation communities, as it highlights and scrutinizes some of the fundamental weak interactions that hold molecules together in solid materials.…”
mentioning
confidence: 99%
“…The increased dispersion interactions due to transition metal coordination make the ferrocene dimer (−3.37 kcal/mol) more stable than the benzene dimer (−2.76 kcal/mol). 28 If the other ligands of the Cp complex are electron-withdrawing (as CO and CN − ), the electrostatic potential surface above the Cp ring in a half-sandwich compound becomes positive, causing very strong stacking interaction between the Cp half-sandwich and benzene (−4.46 kcal/mol) and significantly weaker stacking between two Cp half-sandwich compounds (−2.87 kcal/mol). 28 Stacking with large offsets also depends on both transition metal coordination and the electrostatic potential surface of the Cp ligand.…”
Section: ■ Introductionmentioning
confidence: 99%
“…28 If the other ligands of the Cp complex are electron-withdrawing (as CO and CN − ), the electrostatic potential surface above the Cp ring in a half-sandwich compound becomes positive, causing very strong stacking interaction between the Cp half-sandwich and benzene (−4.46 kcal/mol) and significantly weaker stacking between two Cp half-sandwich compounds (−2.87 kcal/mol). 28 Stacking with large offsets also depends on both transition metal coordination and the electrostatic potential surface of the Cp ligand. It was shown that stacking at large offset is relatively strong if the overlapping edges of molecules have a gradient of electrostatic potential, so that the opposite ends of the potentials overlay.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation